Treatment of a unruptured distal anterior cerebral artery (DACA) aneurysm with pipeline-shield technology: A case report - Zhu Song; Haifeng Yang (Interdisciplinary Neurosurgery, 2025)
A 59 year old female was found to have an aneurysm in the A3 segment of the left anterior cerebral artery during a health examination with using high-resolution magnetic resonance. Oral dual antiplatelet therapy (DAPT) during the perioperative. The third generation Flow diverter of Medtronic Pipeline Flex Embolization Device with Shield Technology (PED-Shield) was implanted into the parent artery for endovascular therapy (EVT). Postoperative instant radiography shows that only the contrast agent is retained at the neck of the aneurysm. Two months after the treatment, the patient stopped taking clopidogrel on their own due to multiple patchy bruises on the skin and used aspirin alone. Four months after the treatment, the patient began to feel intermittent tightness and swelling in the head. Four and a half months after the treatment. DSA showed moderate to severe stenosis in the proximal of the stent, the neck and partial body of aneurysm were visualized, contrast agent retention. We consider it to be stent thrombosis (or excessive intimal hyperplasia) and poor healing of the aneurysm. Our report provides a reference for the feasibility of using PED-Shield to treat distal anterior cerebral artery aneurysms in China; The shaping of the stent catheter sometimes plays a decisive role when PED-Shield used to treat distal aneurysms with large curvature of the parent artery; Also provides evidence that the stent catheter (Phenom 21) unable match the PED-Shield. This also provides case evidence for early Oral dual antiplatelet therapy switched to individual antiplatelet therapy leading to stent thrombosis in PED-Shield.